Amino acid appended cholic acid–azobenzene dyad: an effective & smart phase selective gelator for aromatic solvents. Issue 80 (12th August 2016) - Agarwal, Devesh S.; Gogoi, Neelam; Chowdhury, Devasish; Sakhuja, Rajeev
Abstract : A series of amino acid appended cholic acid–azobenzene dyads have been synthesized and studied for their phase selective gelation behavior, which was further explored for water purification and oil spill remediation. Abstract : A series of amino acid appended cholic acid–azobenzene dyads have been synthesized and studied for their gelation behaviour. One of thel -alanine based dyads showed excellent gelation behaviour in a variety of solvents at room temperature with minimum gel concentration in the range 0.8% (w/v)–1.8% (w/v). The morphology of the stable gels indicated the formation of a lamellar or a dense sheet network in different solvents. Variable temperature 1 H-NMR and FT-IR studies revealed an evident role of intermolecular hydrogen bonding in the self-assembly process. The photo-isomerization between the trans and cis forms of the azobenzene unit was established by UV-visible spectroscopy, and a comparison of 1 H NMR and SEM images of the gel and sol forms. In addition, π → π stacking between phenyl groups of azobenzene might have provided an additional driving force for the formation of a dense three-dimensional network capable of phase selective gelation of aromatic solvents from a water/solvent mixture. This selective gelation of aromatic solvents remains unaffected even in the presence of the common salts usually present in water from different sources. The phase selective gelation ability of the dyad was successfully explored towards the removal of toxic fat-soluble rhodamine dye from water and selectively gelatinizing petrol and crude oil from an oil/water mixture at room temperature. Thus, these smart systems possess the potential to be used effectively in water purification and oil-spill remediation.